Differences in affinity of binding of lymphocytic choriomeningitis virus strains to the cellular receptor alpha-dystroglycan correlate with viral tropism and disease kinetics. - Smelt, S; Borrow, P; Kunz, S; Cao, W; Tishon, A; Lewicki, H; Campbell, K; Oldstone, M (2001)
alpha-Dystroglycan (alpha-DG) was recently identified as a receptor for lymphocytic choriomeningitis virus (LCMV) and several other arenaviruses, including Lassa fever virus (W. Cao, M. D. Henry, P. Borrow, H. Yamada, J. H. Elder, E. V. Ravkov, S. T. Nichol, R. W. Compans, K. P. Campbell, and M. B. A. Oldstone, Science 282:2079-2081, 1998). Data presented in this paper indicate that the affinity of binding of LCMV to alpha-DG determines viral tropism and the outcome of infection in mice. To characterize this relationship, we evaluated the interaction between alpha-DG and several LCMV strains, variants, and reassortants. These viruses could be divided into two groups with respect to affinity of binding to alpha-DG, dependence on this protein for cell entry, viral tropism, and disease course. Viruses that exhibited high-affinity binding to alpha-DG displayed a marked dependence on alpha-DG for cell entry and were blocked from infecting mouse 3T6 fibroblasts by 1 to 4 nM soluble alpha-DG. In addition, high-affinity binding to alpha-DG correlated with an ability to infiltrate the white pulp (T-dependent) area of the spleen, cause ablation of the cytotoxic T-lymphocyte (CTL) response by day 7 postinfection, and establish a persistent infection. In contrast, viruses with a lower affinity of binding to alpha-DG were only partially inhibited from infecting alpha-DG(-/-) embryonic stem cells and required a concentration of soluble alpha-DG higher than 100 nM to prevent infection of mouse 3T6 fibroblasts. These viruses that bound at low affinity were mainly restricted to the splenic red pulp, and the host generated an effective CTL response that rapidly cleared the infection. Reassortants of viruses that bound to alpha-DG at high and low affinities were used to map genes responsible for the differences described to the S RNA, containing the virus attachment protein glycoprotein 1.